IMPLEMENTASI PEMBELAJARAN JASMANI ADAPTIF DALAM MENINGKATKAN KOORDINASI MOTORIK ANAK DENGAN GANGGUAN SPEKTRUM AUTISME - Fadil Yp Maharaja; Mei Engky Saragih; Rutnia Wati Br Panggabean; Carlos Gerson Tarigan; Aryan Syahputra S. Hsb; Borisman Zebua; Yan Indra; Ahmad Sabaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study describes the implementation of adaptive physical education to improve motor coordination in children with autism spectrum disorders (ASD). The challenges faced by children with autism include difficulty controlling body movements, hand-eye coordination, and following complex motor instructions. This study used a descriptive qualitative approach with a case study design at the Harapan Bangsa Special Needs School (SLB) in Medan City. The research subjects consisted of three autistic children aged 7–10 years, one adaptive physical education teacher, and one occupational therapist. Data were collected through participant observation, in-depth interviews, and documentation during eight weeks of adaptive physical education. The research instruments included a physical activity observation guide, a motor coordination assessment sheet, an interview guide, and field notes. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of adaptive physical education, which focused on gross and fine motor activities (such as throwing, catching, jumping, and balancing), significantly improved children's motor coordination skills. Changes were evident in the children's improved balance, synchronized hand-foot movements, and concentration during the activities. Supporting factors for success included adaptive teacher involvement, game-based learning strategies, and a conducive learning environment. Meanwhile, inhibiting factors included limited facilities, children's emotional fluctuations, and a lack of support staff. This study concludes that adaptive physical learning has an important role in improving the motor coordination of autistic children, especially through fun, structured, and individual needs-based physical activities.